Pembuatan REST API Manajemen Data Karyawan Berbasis Website Menggunakan Spring Boot - Adji, Leonard Surya Adji; Mailoa, Evangs (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This study explores the implementation of REST API with Spring Boot in managing employee data in an E-commerce company. With a focus on efficiency, accuracy, and data security, the application utilizes Java, Spring Boot, and MyBatis as the main foundations. System testing demonstrates success in searching, creating, updating, and deleting employee data. Through the Model View Control (MVC) structure, the application ensures clear task separation. This success affirms the application as an effective solution for employee data management, particularly in the dynamic E-commerce industry.